Analysis of Treatment Efficacy of Intense Pulsed Light (M22) for Meibomian Gland Dysfunction with Demodex Mites - Zhang W; Cao X; Yang L; Duan Y; Zhang W (Dove Medical Press, 2023)
Weiliang Zhang,1,* Xiaoqin Cao,2,* Lu Yang,3 Yajian Duan,1 Wei Zhang1 1Department of Ophthalmology, Shanxi Bethune Hospital, Taiyuan, People's Republic of China; 2Department of General Surgery, First Hospital of Shanxi Medical University, Taiyuan, People's Republic of China; 3Department of Ophthalmology, Changzhi Aier Eye Hospital, Changzhi, People's Republic of China*These authors contributed equally to this workCorrespondence: Lu Yang, Changzhi Aier Eye Hospital, Luyangmen Middle Road, Luzhou District, Changzhi, 046000, People's Republic of China, Tel +86-3558128120, Email luyang1494@163.comObjective: To investigate the effectiveness of intense pulsed light (M22) in treating patients with meibomian gland dysfunction (MGD) caused by demodex mites.Methods: A total of 100 patients (100 eyes) diagnosed with demodex mites through microscopic examination at Shanxi Bethune Eye Clinic between June 2021 and May 2023 were selected using convenience sampling. The patients were randomly divided into two groups: an experimental group (n=50) and a control group (n=50). The control group received comprehensive treatment consisting of artificial tears, warm compress, anti-inflammatory eye ointment, hypochlorous acid cleansing, okra cotton pad, and meibomian gland massage. In addition to the comprehensive treatment, the experimental group received intense pulsed light (M22) therapy. After 8 weeks of treatment, the mite clearance rate and cure rate of dry eye were measured for both groups. The recurrence rate of dry eye was also observed 4 weeks after discontinuing M22 treatment.Results: The experimental group achieved a mite clearance rate of 88.0%, while the control group had a rate of 58.0%, with a statistically significant difference (χ2 = 5.43, P = 0.017). Regarding the cure rate of dry eye, the experimental group showed a rate of 92.0%, while the control group had a rate of 82.0%, with a statistically significant difference (χ2 = 3.61, P = 0.021). In terms of the recurrence rate of dry eye, the experimental group exhibited a rate of 13.04%, while the control group had a rate of 26.83%, with a statistically significant difference (χ2 = 4.18, P = 0.016).Conclusion: Intense pulsed light (M22) demonstrated superior efficacy in eradicating demodex mites, treating dry eye, and maintaining the treatment's effectiveness compared to comprehensive treatment with medication in patients suffering from meibomian gland dysfunction with demodex mites.Keywords: intense pulsed light, meibomian gland dysfunction, dry eye